2022
DOI: 10.1063/5.0122858
|View full text |Cite
|
Sign up to set email alerts
|

Charging storage phosphors using a white flashlight via the upconversion approach

Abstract: As an emerging approach to charge storage phosphors, upconversion charging (UCC) is attracting increased attention owing to its fundamental and practical perspectives. Despite the potential, further development of the UCC technology is restricted by the limited types of excitation light sources. Here, we use a white flashlight as excitation to investigate the UCC performance of storage phosphors. We demonstrate, as an example, that a Y3Al2Ga3O12:Pr3+ phosphor exhibits long-lasting emissions in the ultraviolet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The UCC in the phosphor consists of a two-step excitation, which can be achieved through either excited-state absorption or energytransfer upconversion scheme. [33,34] In both schemes, when the phosphor is illuminated by the flashlight, the intermediate state of Cr 3+ is initially populated. Suppose excited-state absorption is the dominant mechanism of excitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The UCC in the phosphor consists of a two-step excitation, which can be achieved through either excited-state absorption or energytransfer upconversion scheme. [33,34] In both schemes, when the phosphor is illuminated by the flashlight, the intermediate state of Cr 3+ is initially populated. Suppose excited-state absorption is the dominant mechanism of excitation.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28] By incorporating the concept of upconverted excitation into the persistent luminescence process, UCC offers practical and fundamental advantages. [25][26][27][28][29][30][31][32][33][34][35][36] It enables effective charging of persistent phosphors using visible or infrared light, thereby overcoming the limitations posed by low-energy light charging. To achieve UCC, the activator ion must possess a long-lifetime intermediate state and a tendency to be oxidized in suitable phosphor systems.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, to further gain insight into the UCC of the LMG:Cr,Yb,Ni phosphors, we study the mechanism that accounts for the upconversion excitation by carrying out an extensive thermoluminescence measurement. During the UCC in the phosphor, in principle, an excited-state absorption or an energy-transfer upconversion mechanism is involved in the two-step excitation. , In either mechanism, upon illumination with the flashlight, the intermediate state of Cr 3+ will be populated first. If the excited-state absorption dominates the UCC excitation process, it is expected that the intense flashlight illumination can promote the Cr 3+ from the intermediate state upward to the high-energy delocalized state.…”
Section: Resultsmentioning
confidence: 99%
“…To date, several low-energy excitation approaches for persistent phosphors have been put forward, in which upconversion charging (UCC) has emerged as an interesting candidate for charging the phosphors using long-wavelength excitation light. It is by now generally accepted that the trap in a phosphor is filled via a two-step ionization of an activator in a typical UCC process. , Moreover, according to the mechanism of UCC, the activator ions should have a tendency to be oxidized in a UCC phosphor. Such a prerequisite limits the choice of activator ion for the UCC design. As candidates for infrared emitting centers in persistent phosphors, rare-earth ions (e.g., Pr 3+ , Nd 3+ , Ho 3+ , Er 3+ , Tm 3+ , or Yb 3+ ) and transition-metal ions (e.g., Cr 3+ , Mn 4+ , or Ni 2+ ) have been reported. , However, many of these ions have no tendency to be oxidized in phosphors and thus do not satisfy the prerequisite for UCC.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we found that the afterglow intensity ratio (AIR) of the present YAG:Tb,Eu phosphor is temperature sensitive in the temperature range from 553 to 803K, with a temperature sensing span of 250 K wider than that of other reported afterglow thermometers. [ 19–24 ] The maximum relative sensitivity of 3.61% K −1 is achieved at 737 K. The temperature‐dependent AIR is attributed to the consequence of that different traps contribute to different afterglow spectra, therefore, leading to the high relative sensitivity and providing a new insight for the development of afterglow thermometers.…”
Section: Introductionmentioning
confidence: 99%